Impact of Human FcγR Gene Polymorphisms on IgG-Triggered Cytokine Release: Critical Importance of Cell Assay Format - Hussain, Khiyam; Hargreaves, Chantal E.; Rowley, Tania F.; Sopp, Joshua M.; Latham, Kate V.; Bhatta, Pallavi; Sherington, John; Cutler, Rona M.; Humphreys, David P.; Glennie, Martin J.; Strefford, Jonathan C.; Cragg, Mark S. (Frontiers in Immunology, 2019)
Monoclonal antibody (mAb) immunotherapy has transformed the treatment of allergy, autoimmunity and cancer. The interaction of mAb with Fc gamma receptors (FcγR) is often critical for efficacy. The genes encoding the low-affinity FcγR have single nucleotide polymorphisms (SNPs) and copy number variation that can impact IgG Fc:FcγR interactions. Leukocyte-based in vitro assays remain one of the industry standards for determining mAb efficacy and predicting adverse responses in patients. Here we addressed the impact of FcγR genetics on immune cell responses in these assays and investigated the importance of assay format. FcγR genotyping of 271 healthy donors was performed using a Multiplex Ligation-Dependent Probe Amplification assay. Freeze-thawed/pre-cultured peripheral blood mononuclear cells (PBMCs) and whole blood samples from donors were stimulated with reagents spanning different mAb functional classes to evaluate the association of FcγR genotypes with T-cell proliferation and cytokine release. Using freeze-thawed/pre-cultured PBMCs, agonistic T-cell-targeting mAb induced T-cell proliferation and the highest levels of cytokine release, with lower but measurable responses from mAb which directly require FcγR-mediated cellular effects for function. Effects were consistent for individual donors over time, however, no significant associations with FcγR genotypes were observed using this assay format. In contrast, significantly elevated IFN-γ release was associated with the FCGR2A-131H/H genotype compared to FCGR2A-131R/R in whole blood stimulated with Campath (p=<0.01) and IgG1 Fc hexamer (p=<0.05). Donors homozygous for both the high affinity FCGR2A-131H and FCGR3A-158V SNPs mounted stronger IFN-γ responses to Campath (p=<0.05) and IgG1 Fc Hexamer (p=<0.05) compared to donors homozygous for the low affinity alleles. Analysis revealed significant reductions in the proportion of CD14hi monocytes, CD56dim NK cells (p=<0.05) and FcγRIIIa expression (p=<0.05), in donor-matched freeze-thawed PBMC compared to whole blood samples, likely explaining the difference in association between FcγR genotype and mAb mediated cytokine release in the different assay formats. These findings highlight the significant impact of FCGR2A and FCGR3A SNPs on mAb function and the importance of using fresh whole blood assays when evaluating their association with mAb-mediated cytokine release in vitro. This knowledge can better inform on the utility of in vitro assays for the prediction of mAb therapy outcome in patients.